PANCASILA SEBAGAI ETIKA DALAM PENGEMBANGAN ILMU DAN TEKNOLOGI DI INDONESIA - Anami, Alya (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2025)
This article delves into Pancasila as a fundamental ethical framework in the development of science and technology (IPTEK) in Indonesia, highlighting its pivotal role in establishing moral guidelines for technological advancements. As the nation's foundational ideology, Pancasila encapsulates five core principles that serve as a compass for the sustainable, equitable, and responsible application of science and technology. These values ensure that technological progress remains rooted in Indonesia’s cultural heritage, respects its national identity, and upholds universal humanitarian ideals. The relevance of Pancasila in IPTEK development becomes increasingly significant in the context of rapid global advancements, where challenges such as social inequality, environmental degradation, and moral erosion pose serious risks. By integrating Pancasila's ethical principles, technological innovation can be steered toward outcomes that benefit society at large, promote environmental stewardship, and safeguard the nation's cultural identity. This ethical approach ensures that technology development in Indonesia transcends mere economic goals, contributing instead to social justice, sustainable development, and the overall well-being of the population. The article underscores the importance of embedding Pancasila's values into every stage of IPTEK development, from research and innovation to application and policymaking. This integration fosters a balanced approach to progress, aligning technological advancements with Indonesia's long-term societal and environmental goals. Furthermore, the discussion emphasizes the need for education systems and public policies to adopt Pancasila-based frameworks, ensuring that future generations of innovators and policymakers prioritize ethical considerations alongside technological excellence. Through this analysis, the article advocates for the application of Pancasila’s values as a guiding light in shaping a technologically advanced yet ethically grounded society. The ultimate vision is to leverage technology as a tool for creating a just, harmonious, and sustainable future for all Indonesians.